Testing model using risk poker technique for scrum-based software development projects / Siti Noor Hasanah Ghazali - Siti Noor Hasanah , Ghazali (2017)
In agile software development, project estimation often depends on group discussion and expert opinions. Literature claims that group discussion in risk analysis helps to identify some of the crucial issues that might affect development, testing, and implementation. However, risks prioritization often relies on individual expert judgement. Therefore Risk Poker, a lightweight risk based testing methodology which helps to achieve consensus through group discussion in risk analysis that outperforms the individual analyst’s estimation is introduced in agile methods. Apart from the above-mentioned benefits Risk Poker can offer, unfortunately no study has been conducted to prove its ability to improve testing process to date. Therefore, this research is aimed at closing this research gap by (i) deploying Risk Poker technique as risk-based strategy in the agile development lifecycle, and (ii) empirically evaluating the proposed test process in providing adequate testing. This research will guide software practitioners in implementing this technique in Scrum-based software development projects. For this purpose, Risk Poker technique is coupled with test coverage for an innovated testing process for Scrum-based software development projects. A case study was conducted with 6 teams of students to estimate test coverage using Risk Poker for an e-commerce system. Three teams estimated their user stories using Risk Poker, while the rest estimated individually and used an average to obtain the statistical combination. The results showed that the proposed usage of Risk Poker mean BRE is 0.24, which is lesser compared to the mean BRE 0.50 for averaged statistical estimation